The care network for drug users: what do professionals say about it? - Antunes da Costa, Pedro Henrique; Federal University of Juiz de Fora. (2016)
This article aimed to understand, from the framework of community psychology, the care network for drug users from professionals’ experiences, and implications of a community level work. Six semi-structured focus groups were conducted with 42 professionals from care networks of four Brazilian cities in the state of Minas Gerais. Data was analyzed through thematic content analysis. Results indicate the need of enhancing network’s operational structure and, mainly, consolidating a comprehensive and continuous care model. Professionals’ critical views of the care network lift a series of contributions to improve it, with the necessity of embracing a community level work and a resources-focus approach to drug abuse. Related to this, there is the necessity to focus care on community and its needs, by understanding it as the main element of care networks for drug users.